Cardiac manifestation of phenylketonuria in adulthood - Péter Homródi; Emese Tóth-Zsámboki; Róbert Gábor Kiss; Orsolya Lovász; Gábor Zoltán Duray (Cardiologia Hungarica)
Introduction: Since the introduction of mandatory infant screening for 26 hereditary metabolic diseases from a drop of blood, many rare diseases – including phenylketonuria (PKU) – have been recognized in time. As a result, the affected population is getting older and due to the higher survival rate, the risk factors associated with the disease and their correlation with cardiovascular diseases can be investigated more widely. Case report: Our case illustrates the cardiovascular manifestations of PKU in adulthood. Our 55-year-old male patient receiving long-term supplementation due to confirmed PKU was diagnosed with heart failure with reduced ejection fraction (HFrEF) during a cardiological control examination, and an intact coronary system was described during the subsequent coronary angiography. In 2023, he was admitted to our department due to cardiac decompensation. Hypertension, elevated LDL-cholesterol level, male gender, obesity and PKU were identified as cardiovascular risk factors. Strategic drug therapy for HFrEF was introduced, with sequential nephron blockade (furosemide, hydrochlorothiazide, eplerenone), his cardiac status was compensated, and his effort dyspnoea and chest discomfort were reduced. During a cardiac MR (magnetic resonance) examination, dilated cardiomyopathy was confirmed. During the control echocardiography performed 3 months after the introduction of the optimal drug therapy and its increase to the maximum tolerable dose, the ejection fraction did not exceed 35%, so the patient received primary prophylactic VVI-ICD implantation. During his cardiological control examinations, the patient's ejection fraction increased compared to the time of the first hospitalization, his complaints decreased, and there was no hospitalization due to repeated cardiac decompensation. Conclusion: PKU is a rare inherited amino acid metabolic disease with widespread complications affecting multiple organ systems. It is associated with several cardiovascular risk factors (hyperlipidemia, hypertension, increased oxidative stress), and has a high rate of cardiovascular complications. In addition, literature data also describe its forms associated with cardiomyopathy. Therefore, close cardiological control examination of these patients, as part of this, echocardiographic follow-up, is essential for timely recognition of complications and their subsequent mitigation.